Is it time to agree upon a standardised approach to the assessment of contributing factors and impacts of adolescent pelvic pain? - Dehlia Moussaoui; Olivia G. Farrell; Sonia R. Grover (Journal of Obstetrics and Gynaecology)
Background A biopsychosocial approach to the understanding of pelvic pain is increasingly acknowledged. However, there is a lack of standardised instruments – or their use – to assess risk factors and their impact on pelvic pain in both clinical and research settings. This review aims to identify validated tools used to assess known contributory factors to pelvic pain, as well as the validated tools to measure the impact of pelvic pain in adolescents and young adults, in order to provide a framework for future standardised, adolescent specific assessment and outcome tools.Methods Literature searches were performed in MEDLINE, PsycInfo and PubMed. Search terms included pelvic pain, dysmenorrhoea, endometriosis, adolescent, pain measurement, quality of life, sleep, mental health, coping strategies and traumatic experience.Results We found validated instruments to assess adverse childhood experiences and coping strategies, both known contributing factors to pelvic pain. The impact of pain was measured through validated tools for health-related quality of life, mental health and sleep.Conclusions Pelvic pain evaluation in adolescents should include a multi-factorial assessment of contributing factors, such as childhood adversity and coping strategies, and impacts of pelvic pain on quality of life, mental health and sleep, using validated instruments in this age group. Future research should focus on the development of consensus amongst researchers as well as input from young women to establish a standardised international approach to clinical trials involving the investigation and reporting of pelvic pain in adolescents. This would facilitate comparison between studies and contribute to improved quality of care delivered to patients.